The measurement of social welfare - Atsushi Tsuneki (Osaka University, Institute of Social and Economic Research (ISER), 2007)
This paper derives a basic formula for the measure of social welfare, a second order approximation to the difference of the value of the Bergson-Samuelson social welfare function between the socially optimal resource allocation and the one in the present suboptimal economy. We discuss pros and cons of our approach for the measurement of welfare compared with other approaches to applied welfare economics, especially the measurement of deadweight loss.
Keywords: H20; D61; D63; 330; Social Welfare; Deadweight Loss; Measurement; Second Order Approximation; Soziale Wohlfahrtsfunktion; Messung; Theorie